1985
DOI: 10.1111/j.1540-8175.1985.tb01255.x
|View full text |Cite
|
Sign up to set email alerts
|

Partial Maze Procedure Is Effective Treatment for Chronic Atrial Fibrillation Associated with Valve Disease

Abstract: The maze procedure may be performed in combination with valve operations to treat chronic atrial fibrillation associated with valve dysfunction. Although we initially used the modified Cox maze III procedure, a more limited partial maze procedure is now preferred because the left atrium might be considered as the electrical impetues for atrial fibrillation. In this study we compared the results of 30 patients (group I) who underwent the full biatrial modified Cox maze III and 20 (group II) patients the partial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(28 citation statements)
references
References 15 publications
0
27
0
1
Order By: Relevance
“…3,4,21,22,24,25,27,31,32,37 The remaining 15 studies (53.6%) were retrospective observational, of which 3 were propensity adjusted. 5,19,20,26,[28][29][30]33,34,38,39,[44][45][46][47] In 16 studies (57.1%) all the patients enrolled presented exclusively non-paroxysmal AF forms and these studies constituted the "non-paroxysmal AF subgroup." [20][21][22][23][25][26][27][28][34][35][36][37][38][39]46,47 clearly specify the types of AF included.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…3,4,21,22,24,25,27,31,32,37 The remaining 15 studies (53.6%) were retrospective observational, of which 3 were propensity adjusted. 5,19,20,26,[28][29][30]33,34,38,39,[44][45][46][47] In 16 studies (57.1%) all the patients enrolled presented exclusively non-paroxysmal AF forms and these studies constituted the "non-paroxysmal AF subgroup." [20][21][22][23][25][26][27][28][34][35][36][37][38][39]46,47 clearly specify the types of AF included.…”
Section: Discussionmentioning
confidence: 99%
“…28,31,32,46 CM3 or CM3 plus RF ablation or cryoablation were used in four studies. 3,4,27,38 Criteria to decide between BA and LA approach were randomization in three RCT, 23,35,36 clinical characteristics (ie, AF duration, LA size) in two studies, 24,32 BA approach when the RA was already open for a right-sided procedure (ie, tricuspid repair) in two studies, 33,37 serial timeframes (from 1994 to 1997 BA and subsequently LA approach) in one study, 38 Instead, for non-randomized studies, the Newcastle-Ottawa Scale score ranged between 5 and 7 for any of the included studies (mean 6.1 ± 0.5): as shown in Supplementary Material S2, none of the studies took a point either for question S3 and S4 since none of these studies had a control group with healthy voluntary patients, limiting the maximum achievable score for any of the included study to 7.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In all, 21 studies were included in this meta-analysis, including three prospective randomized trials [ 23 25 ], five prospective observational studies [ 13 , 26 29 ], and 13 retrospective observational studies [ 8 , 12 , 14 , 15 , 21 , 22 , 30 36 ]. The risk of bias in each study is shown in Figure 2 and Table 1 .…”
Section: Methodsmentioning
confidence: 99%
“…На данный момент сравнительная эффективность биатриальной (БА) и левопредсердной (ЛП) схем фрагментации остается сложным предметом дискуссии для современных клиницистов и хирургов. В современных исследованиях, включая 2 рандомизированных [7,8] и 4 ретроспективных обсервационных исследования [9][10][11][12], показана сопоставимая эффективность как левопредсердной (ЛП), так и биатриальной (БА) абляции [11,13]. В то же время другие исследования [14][15][16], включая 2 метаанализа, показывают, что БА абляция способствует более длительной свободе от возврата ФП.…”
unclassified